2019
DOI: 10.3991/ijoe.v15i11.10651
|View full text |Cite
|
Sign up to set email alerts
|

Differential Evolution in Wireless Communications: A Review

Abstract: <p class="0abstract">Differential Evolution (DE) is an evolutionary computational method inspired by the biological processes of evolution and mutation. DE has been applied in numerous scientific fields. The paper presents a literature review of DE and its application in wireless communication. The detailed history, characteristics, strengths, variants and weaknesses of DE were presented. Seven broad areas were identified as different domains of application of DE in wireless communications. It was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 160 publications
(159 reference statements)
0
5
0
Order By: Relevance
“…Presentation of the detailed history, characteristics strengths, variants and weaknesses of DE are made in [4]. Identification of seven broad areas are made as different domains of application of DE in wireless communications it was observed that the two major areas where the DE is applied are the coverage area maximization and energy consumption minimization.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Presentation of the detailed history, characteristics strengths, variants and weaknesses of DE are made in [4]. Identification of seven broad areas are made as different domains of application of DE in wireless communications it was observed that the two major areas where the DE is applied are the coverage area maximization and energy consumption minimization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Optimization is a very important topic because it helps to find the best solution from the number of solutions. Hence optimized chaotic code plays a very important role in wireless communication techniques [3], [4]. Considering optimization, Differential evolution (DE) is an important evolutionary technique, enhances its parameters such as, initialization of population, mutation, crossover, etc.…”
Section: Introductionmentioning
confidence: 99%
“…DE is applied as clustering algorithm in order to ensure minimal energy consumption and network resilience and sustainability [37]. Other applications can be seen in [38][39][40].…”
Section: Differential Evolution In Wireless Communicationmentioning
confidence: 99%
“…However, they generate results from the example that they process. ANN is a member of evolutionary computational methods [9].…”
Section: Introductionmentioning
confidence: 99%